ScS-triggered slip on megathrust interfaces after the 2011 M W 9.0 Tohoku-Oki earthquake - Sunyoung Park; Hiroo Kanamori; Luis Rivera (Science, 2026)
We report an extraordinary observation of ground motion in Japan after the moment magnitude ( M W ) 9.0 2011 Tohoku-Oki earthquake attributed to a multiplate-interface slip event triggered by shear wave that traveled to the Earth’s core and back. The megathrust earthquake generated a strong ScS phase with a peak-to-peak amplitude exceeding 1 centimeter in Japan. Superposed on this waveform, an eastward steplike displacement of up to 5 to 6 millimeters was recorded in Global Navigation Satellite System (GNSS) data throughout Japan. This likely originated from slip on the megathrust interfaces triggered by the nearly simultaneous arrival of the ScS wave across Japan. Such an ScS triggering is a previously unrecognized source of seismic hazard, which can potentially (re)activate the mainshock area and the broader surrounding megathrust interfaces.